p-GaN/n-IGZO self-powered ultraviolet photodetector with ultralow dark current and high sensitivity - Liao, Yikai (2024)
Self-powered ultraviolet (UV) photodetector has attracted growing research interest for applications in biological and human related fields with a low power consumption. However, typical construction strategies of heterojunction require materials with high crystal quality to realize high device performance with low dark current, which normally necessitates costly thin film epitaxy process. In our study, a high sensitivity self-powered UV photodetector with an ultralow dark current has been proposed by constructing p-GaN/n-IGZO heterojunction via a facile room temperature sputtering of IGZO thin film on commercially available p-GaN/sapphire substrate. By implementing UV-Ozone surface treatment to introduce an ultrathin oxide layer in the junction interface, dark current of the photodetector can be as low as 0.45 pA, which leads to a high detectivity of 1.9 × 1013 Jones with a rise time of 0.92 ms and a decay time of 11.61 ms when operating in self-powered mode. Our work has put forward a facile and cost-effective route for developing highly sensitive UV detecting devices with a low dark current and a low power consumption, which paves the path to advances in green industry of UV optoelectronics.